2021
DOI: 10.1002/adfm.202104976
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of CO2 Molecular Activation and 4f Levels as Electron Transport Bridge in Dysprosium Single Atom Composite Photocatalysts with Enhanced Visible‐Light Photoactivities

Abstract: Environmental and energy issues are the two main challenges that hinder the sustainable development of human society. [1][2][3][4][5][6] Solar energy has attracted urgent attention due to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…44,[71][72][73] CO 2 reduction,45,62,[74][75][76] N 2 reduction,63,77,78 C-O coupling,65 pollutant degradation, 79,80 CH 4 conversion,68 H 2 O 2 production,69 as well as photocatalytic sensing 70,81,82. …”
mentioning
confidence: 99%
“…44,[71][72][73] CO 2 reduction,45,62,[74][75][76] N 2 reduction,63,77,78 C-O coupling,65 pollutant degradation, 79,80 CH 4 conversion,68 H 2 O 2 production,69 as well as photocatalytic sensing 70,81,82. …”
mentioning
confidence: 99%
“…The large atomic radius of Gd results in quite a small number of Gd atoms being loaded into CB. [18] On the contrary, the graphite stripes disappear and the new Ni (111) crystal planes emerge in CBNNiGd-700 and CBNNi-700, implying that Ni with the relatively small atomic radius is readily incorporated into the graphite lattices of CB, which can generate defect sites. [23] As revealed by the elemental mapping images, Ni atoms agglomerate into nanoparticles encapsulated in the carbon matrixes of CBNNiGd-700 and CBNNi-700, [11] while the relatively uniform dispersion of Gd atoms is accomplished within CBNNiGd-700 and CBNGd-700.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Recent reports have demonstrated that LMs can be loaded onto various supports and employed in a variety of catalytic reactions. [18,19] LMs with the comparatively large ion radii are able to induce lattice distortion and deformation stress of supports, conducive to the formation of defect sites. [19] In the meantime, the strong lanthanide contraction effect of LM atoms can change the local electron densities of the surrounding atoms and optimize the electronic states of the supports, in favor of the elevation of adsorption capabilities of catalyst surfaces and thereby the strengthening of catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…As another excellent catalyst material, CdS has been widely used in hydrogen production from water splitting and photocatalytic degradation of organic pollutants. [29][30][31][32][33] CdS has high visible light response and carrier transport ability. More importantly, the suitable band gap (2.4 eV) of CdS can be well matched with that of InVO 4 ; so it is possible to form a Type-II heterostructure.…”
Section: Introductionmentioning
confidence: 99%